Creating successful second tier cities in Europe - messages from ESPON. - Parkinson, Michael; Evans, Richard (Informationskreis für Raumplanung, 2012)
The global recession and Eurozone crisis have had a huge impact upon the European economy and present even greater future threats. They have sharpened the debate about policies for national competitiveness. They have also sharpened the debate about the economic contribution of capital and second tier cities and whether countries perform better if they concentrate their investment in their national capitals or spread investment across a wider set of cities. They pose a single crucial question: Why should policy makers invest beyond the capital cities in an age of austerity? This debate will become more important during the next decade as the crisis threatens to undermine the real achievements made by many European cities.
Keywords: Raumordnung; Raumentwicklung; Raumstruktur; Regionalentwicklung; Regionale Disparität; EU-Programm; EU-Projekt; Raumentwicklungspolitik; Entwicklungsplan; Wettbewerbsfähigkeit; Polyzentralität; Dezentralisierung; Städtesystem